Effect of Window Overhang Shade on Heat Gain of Various Single Glazing Window Glasses for Passive Cooling. (2016) - Shaik, Saboor; Gorantla, KiranKumar; Setty, Ashok Babu Talanki Puttaranga
Abstract: This paper presents thermal performance of various single glazing window glasses covered with and without window overhang shading. Buildings are designed with laterite stone walls with different dimensions of overhang shading devices on single glazing windows in four different climatic zones of India: Ahmedabad (Hot & dry), Bangalore (moderate), Calcutta (warm & humid) and Hyderabad (composite). In this study, five glass materials such as clear, bronze, green, grey and blue-green were selected. Total three hundred and twenty building models with and without window overhangs were designed in four climatic zones of India using Design builder 4.3.0.039. Thermal simulation was carried out in Energy plus 8.1 simulation tool. From the results, it is observed that laterite buildings with grey glass window with 1.5m overhang shading device were found to be energy efficient from the least heat gain point of view in south direction among three hundred and twenty building models studied in four climatic zones of India. The results of the study help in selecting the best window glass material and also help in selecting appropriate dimensions for overhang shading device for reducing cooling loads in buildings.